1992
DOI: 10.1159/000118828
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age on Event-Related Potentials in Chronic Alcoholics: A Multimodal Study

Abstract: To test different versions of the premature aging hypothesis in alcoholics, brainstem auditory evoked potentials (BAEPs), long-latency auditory evoked potentials (LAEPs), P3 and visual evoked potentials (VEPs) were recorded in 32 alcoholic subjects. The phenomena in patients’ event-related potentials (ERPs) differ from those observed in normal aging subjects and become more pronounced with age. ANOVA showed a significant effect by group (alcoholic patients/controls) on certain parameters of BAEPs (III, III-V, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(24 reference statements)
0
9
0
1
Order By: Relevance
“…Numerous studies have reported the susceptibility of elderly alcoholics to the effects of alcohol (Berglund et al, 1987;Biggins et al, 1995;Cadaveira et al, 1992;Di Sclafani et al, 1995;Hellstrom-Lindahl et al, 1993;Hesselbrock et al, 1985;Pfefferbaum et al, 1997). Here, a significant Group X Age interaction was found in an ANOVA run on MMN amplitude, after alcoholic and control groups were divided into young and old subgroups.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Numerous studies have reported the susceptibility of elderly alcoholics to the effects of alcohol (Berglund et al, 1987;Biggins et al, 1995;Cadaveira et al, 1992;Di Sclafani et al, 1995;Hellstrom-Lindahl et al, 1993;Hesselbrock et al, 1985;Pfefferbaum et al, 1997). Here, a significant Group X Age interaction was found in an ANOVA run on MMN amplitude, after alcoholic and control groups were divided into young and old subgroups.…”
Section: Discussionmentioning
confidence: 65%
“…Numerous studies have indicated that the toxic effects of alcohol on the brain may be exacerbated by age (Berglund et al, 1987;Biggins et al, 1995;Cadaveira et al, 1992;Di Sclafani et al, 1995;Hellstrom-Lindahl et al, 1993;Hesselbrock et al, 1985;Pfefferbaum et al, 1997). Further-more, some neurocognitive abnormalities associated with alcohol consumption are only, or more easily, evident in older subjects ( Berglund et al, 1987;Cadaveira et al, 1992;Hesselbrock et al, 1985).…”
mentioning
confidence: 99%
“…De hecho, durante un buen número de años algunos índices comportamentales (efectos sedativos, sobre coordinación motora) llevaron a pensar que los jóvenes eran menos vulnerables a la acción del alcohol. Las principales variantes de la hipótesis del envejecimiento prematuro partían de este supuesto y apuntaban a más allá de los 40 años como etapa especialmente crítica 11 .…”
Section: Un Patrón Con Elevados Costes Socialesunclassified
“…The combination of age and other factors that impair hearing, such as noise [13], ototoxic agents [14], alcohol [15] and irradiation [16], has been studied, but little information is available concerning the susceptibility of the elderly cochlea to infections. Though chronic suppurative otitis media is rare among the elderly, it is often caused by Pseudomonas aeruginosa [17].…”
Section: Introductionmentioning
confidence: 99%